2007
DOI: 10.1080/15389580701272346
|View full text |Cite
|
Sign up to set email alerts
|

Factors Leading to Older Drivers' Intersection Crashes

Abstract: Factors leading to intersection crashes vary with age, even between two age groups of older drivers. Because the number of older drivers is projected to increase, it is important to identify ways to reduce the frequency and severity of their intersection crashes. Roundabouts and protected left turn lanes at signalized intersections may help to reduce failure-to-yield crashes at intersections, especially among older drivers. Crash avoidance systems may help to reduce crashes for drivers of all ages, but most sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 24 publications
1
49
0
1
Order By: Relevance
“…In the present study, certain driving errors were more common than others in the older drivers group, e.g. speed adjustment and positioning, and these errors do predict crashes in older drivers [32,33] . Furthermore, and similar to our findings, Reason et al [31] found frequent driving errors regarding gear changing.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, certain driving errors were more common than others in the older drivers group, e.g. speed adjustment and positioning, and these errors do predict crashes in older drivers [32,33] . Furthermore, and similar to our findings, Reason et al [31] found frequent driving errors regarding gear changing.…”
Section: Discussionmentioning
confidence: 86%
“…Approaching and crossing an intersection involves several processes resulting in a complex task. Crossing an intersection requires divided attention among several pieces of information, perceiving and processing changes in the traffic situation, perceiving and processing signals and traffic signs, determining and executing a course of action (Braitman et al, 2007), and decision making under time pressure (Brouwer & Ponds, 1994). Attentional capacity deficits seem to be the key for their increased involvement in accidents (Owsley et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Male drivers were involved in 53% of driving violations ( = 3031) and female in about 47% ( = 2648). Young drivers (ages [15][16][17][18][19][20][21][22][23][24] were engaged in 30% of driving violations ( = 1696) and old drivers (ages 65+) in approximately 13% ( = 769). About 44% of driving violations ( = 2511) occurred in the urban settings, and 17% of driving violations ( = 982) took place in rural environment.…”
Section: Resultsmentioning
confidence: 99%
“…Romano et al [16] found that race/ethnicity appeared to be an important reason for fatal stop sign running crashes. Braitman et al [17] formed a conclusion that failure to yield to right-of-way was the contributing factor leading to majority of older drivers' crashes at the intersections controlled by stop signs. Keay et al [18] uncovered the differences in older drivers' failure to stop at stop signs under the urban and rural environments.…”
Section: Introductionmentioning
confidence: 99%